Modelling thermal phosphorus recovery from sewage sludge ash. (December 2016) - Arnout, Sander; Nagels, Els
Abstract: Phosphorus is an essential and irreplaceable element for life, and its growing production is mainly based on the processing of non-renewable phosphate ores, often extracted in regions with political instability risks, making it a critical element. An alternative phosphorus source, explored in the RecoPhos project, is found in sewage sludge ash. In this project, an inductively heated packed carbon bed reactor has been developed to treat the ashes at high temperature. Phosphorus is recovered by reduction and vaporization, and can be recovered as white phosphorus or phosphoric acid. In order to describe the chemistry and predict the potential outputs and yields, InsPyro has developed thermodynamic models for the system and the reactor. The results for the reduction behavior of slag, ferrophosphorus formation, and overall P recovery show good agreement with lab and pilot scale tests. Using the model, optimal reduction and fluxing parameters can be determined. Highlights: Thermodynamic model for phosphorus reduction and volatilization. Phosphorus recovery to gas limited by iron alloy formation. Considerable evolution in slag composition during reduction.